Comparative Analysis and Modeling of Superoxide Dismutases (SODs) in Brachypodium distachyon L. - ÖZYİĞİT, İBRAHİM İLKER (SPRINGER, 2014)
Superoxide dismutase (SOD, EC 1.15.1.1) is an enzyme catalyzing the dismutation of superoxide radical to hydrogen peroxide and dioxygen. To date, four types of SODs - Cu/ZnSOD, MnSOD, FeSOD, and NiSOD - have been identified. In this study, SOD proteins of Brachypodium distachyon (L.) Beauv. were screened by utilization of bioinformatics approaches. According to our results, Mn/FeSODs and Cu/ZnSODs of B. distachyon were found to be in basic and acidic character, respectively. Domain analyzes of SOD proteins revealed that iron/manganese SOD and copper/zinc SOD were within studied SOD proteins. Based on the seconder structure analyzes, Mn/FeSODs and Cu/ZnSODs of B. distachyon were found as having similar sheets, turns and coils. Although helical structures were noticed in the types of Mn/FeSODs, no the type of Cu/ZnSODs were identified having helical structures. The predicted binding sites of Fe/MnSODs and Cu/ZnSODs were confirmed for having His-His-Asp-His and His-His-His-Asp-Ser residues with different positions, respectively. The 3D structure analyzes of SODs revealed that some structural divergences were observed in patterns of SODs domains. Based on phylogenetic analysis, Mn/FeSODs were found to have similarities whereas Cu/ZnSODs were clustered independently in phylogenetic tree.
Keywords: Superoxide dismutase; Antioxidant proteins; Brachypodium distachyon; 3D modeling; In silico analysis; ESCHERICHIA-COLI; PROTEIN; EVOLUTION; STRESS; GENE; MITOCHONDRIAL; PHYLOGENIES; EXPRESSION; PREDICTION; ENZYME